Effleurage Massage as a Non-Pharmacological Intervention to Reduce Back Pain in Third Trimester Pregnant Women: A Literature Review (Jurnal kesehatan komunitas (Journal of community health), 2026)
Lower back pain is a common complaint experienced by pregnant women in the third trimester due to biomechanical changes during pregnancy and can interfere with daily activities. This research aims to assess the effectiveness of effleurage massage in reducing lower back pain in pregnant women in the third trimester. The research method used a literature review of four articles from international and national journals published between 2021 and 2025. Article searches were conducted through Wiley Online Library, Google Scholar, and Sage Journals using the keywords "Effleurage Massage," "Back Pain," and "Pregnant." Of the 2,322 articles found, four relevant articles were selected based on exclusion and inclusion criteria. The analysis was conducted descriptively. The results indicate that effleurage massage is effective, safe, and easy to implement in reducing lower back pain in pregnant women in the third trimester. Therefore, effleurage massage is recommended as a non-pharmacological intervention in antenatal care services by midwives.
Keywords: Pregnant Women, Non-Pharmacological Interventions, Pregnancy, Back Pain, Effleurage Massage, Third Trimester